Selective Utilization of Organic Solid Wastes by Earthworm (Eisenia foetida) - Pant, Shankar Raj; Yami, Kayo Devi (Nepal Journal of Science and Technology, 2010)
Rapid growth of population in Kathmandu valley has increased solid wastes generation tremendously. One of the best ways of managing the organic wastes is to recycle domestic wastes at the site of its origin by vermicomposting into valuable organic fertilizers. A laboratory experiment was carried out at for proper management of solid wastes of Kathmandu valley, generated from Ayurveda industry, sugar mill (bagasse), wood mill, kitchen, and vegetable and fruit markets. The experiment dealt with the decomposition of solid wastes through the action of red worm (Eisenia foetida). The vermicomposting of mixtures were carried out for 12 weeks. Observations showed that vermicompost obtained from Ayurveda industry wastes was found to be rich in N, P, K and organic matter, and vermicompost from sugarcane bagasse was found best for rapid multiplication of Eisenia foetida. Fish scales and sawdust were identified as worst substrate for this worm. Key words: vermi compost; organic solid wastes; Eisenia foetida DOI: 10.3126/njst.v9i0.3172 Nepal Journal of Science and Technology 9 (2008) 99-104